The Cooperation between the European Union and Egypt in the field of Migration (A case study on Egypt-Italy Migration Dynamics) - (:unkn) unknown (My University, 2023)
Migration between Egypt and the European Union is a phenomenon of significant importance in the current global context.While migratory movements have always been a crucial part of human history, the specific dynamics of Egyptian-European migration arouse particular interest due to their political, economic and social implications. From this perspective, this thesis in international law, which also addresses the European Union's external action in the field of migration, focuses on the study of migratory cooperation between the European Union, ranked as the world's top destination for immigration in 2022, and Egypt, considered as the primary African country of emigration. This study centers on the analysis of the mechanisms for implementing this cooperation and identifies their potential limitations. This work is structured around two major axes: firstly, the study of the departure of Egyptian emigration flows towards the European Union, and secondly, the analysis of the arrival of these flows on the territory of the Union. The main objective is to explore in depth the particularities of the Egyptian migration system, which plays a crucial role not only as a country of departure to European countries, but also as a transit country for migrants from neighboring countries in Africa and the Middle East seeking to reach Europe. Thus, special attention is given to the impact of Egypt's position as a migratory crossroads and point of convergence between Africa, the Middle East, and the European Union, highlighting its specificity in the Euro-Mediterranean and Euro-African migratory context compared to other neighboring countries. The aim of this study is to examine the various frameworks of migratory cooperation between Egypt and the European Union, both at the bilateral and regional levels, while analyzing their different legal aspects. Although the cooperation between Egypt and the European Union in migration matters is well-founded on soft law instruments,
Keywords: African Research